The Role of Nutritional Habits and Moderate Red Wine Consumption in PON1 Status in Healthy Population - Fidel Navarro-García; Néstor Ponce-Ruíz; Aurora Elizabeth Rojas-García; Gabriela Ávila-Villarreal; José Francisco Herrera-Moreno; Briscia S. Barrón-Vivanco; Yael Y. Bernal-Hernández; Cyndia Azucena González-Arias; Irma Martha Medina-Díaz (Applied Sciences, 2021)
Paraoxonase 1 (PON1) plays a role as antioxidant on HDL. Including in diet additionally ingest of polyphenolic compounds can stimulate PON1 transcription and increase its activity. The aim of this study was to evaluate the effect of dietary intake, red wine consumption, and PON1 genotypes (Q192R, L55M and C-108T) on the specific activity of PON1 in a healthy population. A descriptive and analytical pilot study was conducted in Mexican volunteers clinically healthy (n = 45) aged from 21–59 years. Over 6 weeks, the study participants ingested 120 mL of red wine per day. PON1 concentration, PON1 activities, genetic polymorphisms and dietary intake were evaluated. The preliminary fingerprinting of the wine was determined to corroborate the presence of phenolic compounds such as tannins and gallotannins. Neither dietary intake nor PON1 genotypes showed an effect on the specific activity of PON1. However, a significant increase in specific AREase activity after red wine consumption period was observed in the study participants. Our data suggest that the moderate consumption of red wine has a beneficial effect on PON1 specific AREase activity in this healthy Mexican population.